Determination of the 15N chemical shift anisotropy in natural abundance samples by proton‐detected 3D solid‐state NMR under ultrafast MAS of 70 kHz. (12th February 2019) - Rossi, Federica; Duong, Nghia Tuan; Pandey, Manoj Kumar; Chierotti, Michele R.; Gobetto, Roberto; Nishiyama, Yusuke
Abstract: Chemical shift anisotropy (CSA) is a sensitive probe of electronic environment at a nucleus, and thus, it offers deeper insights into detailed structural and dynamic properties of different systems, for example, chemical, biological, and materials. Over the years, massive efforts have been made to develop recoupling methods that reintroduce CSA interaction under magic angle spinning (MAS) conditions. Most of them require slow or moderate MAS (≤20 kHz) and isotopically enriched samples. On the other hand, to the best of the authors' knowledge, no 13 C or 15 N CSA recoupling schemes at ultrafast MAS (≥60 kHz) suitable for cost‐effective natural abundant samples have been developed. We present here a proton‐detected 3D 15 N CS/ 15 N CSA/ 1 H CS correlation experiment which employs 1 H indirect detection for sensitivity enhancement and a γ‐encoded RN n ν ‐symmetry‐based CSA recoupling scheme. In particular, two different symmetries, that is, R8 3 7 and R10 4 9, are first tested, in a 2D 15 N CSA/ 1 H CS version, on [U‐ 15 N]‐L‐histidine·HCl·H2 O as a model sample under 70 kHz MAS. Then the 3D experiment is applied on glycyl‐L‐alanine at natural abundance, resulting in site‐resolved 15 N CSA lineshapes from which CSA parameters are retrieved by SIMPSON numerical fittings. We demonstrate that this 3D R‐symmetry‐based pulse sequence is highly robust with respect to wide‐range offset mismatches and weakly dependent to rf inhomogeneity within mis‐sets of ±10% from the theoretical value. Abstract : Proton detected 3D 15 N CS/ 15 N CSA/ 1 H CS correlation experiments are demonstrated. 15  N CSA recoupling sequences are designed for fast MAS conditions around 70 kHz. 15  N CSA at natural abundance is determined.